University research funding: Why does industry funding continue to be a small portion of university research, and how can we change the paradigm?. Issue 3 (June 2021) - Pourdeyhimi, Behnam
In the USA, the federal government is still the chief source of external funding for R&D across all industries and academia. Industry funding for universities continues to remain low. There have been many attempts to increase the interactions between industry and academia and, while there is a great deal of interest in building public–private partnerships, the results have not been promising. In this article, the author analyzes data from a number of government sources and other organizations to provide a full picture of the funding landscape in the USA. Some thought is given to why such interactions have not been successful and how we may be able to realign university activities and policies to embrace partnerships with industry.